Hubungan Fungsi Kognitif Dengan Tingkat Kemandirian Activity Of Daily Living (Adl) Pada Lansia Dikelurahan Singkil 1 Lingkungan 6 Kota Manado - Yuliana Sako; I Made Rantiasa; Bayu Dwisetyo (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
The elderly is a process of the final stage of human life that will be lived by everyone. Cognitive function indicates the process of receiving, organizing and interpreting stimulus sensors to think and solve problems. The purpose of this study was to determine the relationship between cognitive ability and the level of independence of Activity Of Daily Living (ADL) in the elderly in Singkil 1 sub-district 6 Manado city This research uses a correlational analytical method with the approach used is a time series, which is a type of data consisting of variables collected according to time sequence in a certain time span. The sample of this study amounted to 42 respondents using the Purposive Sampling technique. Data collection was taken using questionnaire sheets. Furthermore, the data that has been collected is then analyzed using the Chi-square statistical test with a significant level (α) of 0.05 The results showed that the most respondents' gender was women, namely 35 respondents with a percentage (83.3%), the most respondents did not attend school, namely 28 respondents with a percentage (66.7%), the most respondents' jobs as IRT were 35 respondents with a percentage (83.3%), and the results of statistical tests found a significant relationship between cognitive function and the level of independence of the elderly with p-value = 0.002